Economic Analysis of Irrigation Expenditure Policies in Uzbekistan (European Journal of Economics, Finance and Business Development, 2023)
This research paper aims to conduct an economic analysis of irrigation expenditure policies in Uzbekistan. The study investigates the budget allocation and effectiveness of irrigation expenditures, focusing on the impact of different policies on the agricultural sector, economic growth, and sustainable water resource management. By evaluating the current irrigation expenditure framework, the paper seeks to provide recommendations for optimizing resource allocation, improving cost-effectiveness, and enhancing the overall efficiency of irrigation investments. The findings of this research can inform policy decisions and contribute to the sustainable development of Uzbekistan's agricultural sector.